Methamphetamine and the hypothalamic-pituitary-adrenal axis - Zuloaga, Damian G.; Jacobskind, Jason; Raber, Jacob (Frontiers in Neuroscience, 2015)
Psychostimulants such as methamphetamine (MA) induce significant alterations in the function of the hypothalamic-pituitary-adrenal (HPA) axis. These changes in HPA axis function are associated with altered stress-related behaviors and might contribute to addictive processes such as relapse. In this mini-review we discuss acute and chronic effects of MA (adult and developmental exposure) on the HPA axis, including effects on HPA axis associated genes/proteins, brain regions, and behaviors such as anxiety and depression. A better understanding of the mechanisms through which MA affects the HPA axis may lead to more effective treatment strategies for MA addiction.